Nanomaterials for Tumor Hypoxia Relief to Improve the Efficacy of ROS-Generated Cancer Therapy - Ruan, Changping; Su, Kaihua; Zhao, Dongmin; Lu, Ai; Zhong, Chaoran (Frontiers in Chemistry, 2021)
Given the fact that excessive levels of reactive oxygen species (ROS) induce damage to proteins, lipids, and DNA, various ROS-generating agents and strategies have been explored to induce cell death and tumor destruction by generating ROS above toxic threshold. Unfortunately, hypoxia in tumor microenvironment (TME) not only promotes tumor metastasis but also enhances tumor resistance to the ROS-generated cancer therapies, thus leading to ineffective therapeutic outcomes. A variety of nanotechnology-based approaches that generate or release O2 continuously to overcome hypoxia in TME have showed promising results to improve the efficacy of ROS-generated cancer therapy. In this minireview, we present an overview of current nanomaterial-based strategies for advanced cancer therapy by modulating the hypoxia in the TME and promoting ROS generation. Particular emphasis is put on the O2 supply capability and mechanism of these nanoplatforms. Future challenges and opportunities of design consideration are also discussed. We believe that this review may provide some useful inspiration for the design and construction of other advanced nanomaterials with O2 supply ability for overcoming the tumor hypoxia-associated resistance of ROS-mediated cancer therapy and thus promoting ROS-generated cancer therapeutics.